Health Promoting Behaviors and its Related Factors in Elderly - A. Habibi; S. Nikpour; M. Seyedoshohadaei; H. Haghani (Iran University of Medical Sciences, 2006)
Background & Aim: Long life expectancy and living healthy in the stage of elderly is a human right, thus health promoting behaviours for prevention of complications are important. The purpose of this study was to determine health promoting behaviors and its related factors in elderly people.   Material & Method: This was a descriptive and cross-sectional study. Through multi-stage sampling method, 410 participants who were 60 years old and more, selected to contribute in the study . A questionaire was used to collect data by interview.   Resulth: The results showed that 'smoking cessation' behaviour had significant relationships (P<0.05) with gender and current health status. Also smoking abstinence' behaviour had statistical significant correlation with gender, education and current health status. Moreover, 'exercise (walking) behaviour had significant correlation with gender, family structure and current health status 'low-salt diet' and 'low fat diet' had significant correlation with gender, education and current health status. In addition 'milk consumption, had significant relationship with age, familystructure, current health status 'health check up', 'Blood Pressure check up' and economic status (P<0.05).   Conclusion: According to the study findings, it is concluded that different factors could correlate with health promoting behaviors in elderly people. Therefore, planning for health promotion based on the correlated factors, social contribution, improving medical and health services and connseling services in elderly population is important to be considered.